Targeted Genetic Sequencing Analysis of 223 Cases of Pseudomyxoma Peritonei Treated by Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy Shows Survival Related to GNAS and KRAS Status - Jane Gibson; Reuben J. Pengelly; Amatta Mirandari; Konstantinos Boukas; Sophia Stanford; Thomas Desmond Cecil; Faheez Mohamed; Sanjeev Paul Dayal; Alexios Tzivanakis; Brendan John Moran; Alex Mirnezami; Norman John Carr; et al. (Cancer Medicine)
ABSTRACT Background and Aim Pseudomyxoma peritonei (PMP) is an unusual condition with unique behaviour caused by a mucinous neoplasm, usually arising from the appendix. The aim of this study was to evaluate the prevalence of genomic alterations in clinical specimens of PMP using a targeted assay and correlate the findings with clinical, pathological and outcome data. Sequencing data from 223 patients were analysed. Results The median follow‐up interval was 48 months. The primary neoplasm was appendiceal in 216 patients, ovarian in 4, urachal in 2 and renal in one. We confirmed common mutations in GNAS and KRAS (42% each) with significant co‐occurrence of variants in these genes. TP53 mutations were found in 8%. Other mutations were rare but included novel mutations in BAP1 and ERBB4. Of 17 patients with acellular peritoneal mucin, 6 (35%) were positive for DNA mutations. The non‐appendiceal cases generally showed a similar mutational landscape to the appendiceal lesions with GNAS and KRAS commonly mutated, although one urachal lesion showed multi‐hit TP53 mutation without variants in either GNAS or KRAS. Survival was significantly associated with the grade of the primary neoplasm, the grade of the peritoneal disease, the completeness of cytoreduction score and with mutation in either GNAS, KRAS or both. The hazard ratio (HR) associated with mutation in GNAS and/or KRAS was 1.87 (p = 0.004). Conclusions Survival outcome was more closely associated with the grade of the peritoneal disease than with the grade of the primary neoplasm. Our findings support the developing concept that mutational analysis may provide prognostic information in patients with PMP.